2009
DOI: 10.2139/ssrn.1342566
|View full text |Cite
|
Sign up to set email alerts
|

Bank Ownership, Firm Value and Firm Capital Structure in Europe

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
3
8
1
Order By: Relevance
“…Banks are motivated by the resolution of shareholders-debtholders conflicts. These results confirm those of Barucci and Mattesini (2008) for Italian firms, Baert and Vennet (2009) for European firms and Lin et al (2009) for Chinese firms.…”
Section: Bank Shareholding and The Shareholders-creditors Conflictsupporting
confidence: 85%
“…Banks are motivated by the resolution of shareholders-debtholders conflicts. These results confirm those of Barucci and Mattesini (2008) for Italian firms, Baert and Vennet (2009) for European firms and Lin et al (2009) for Chinese firms.…”
Section: Bank Shareholding and The Shareholders-creditors Conflictsupporting
confidence: 85%
“…The capital structure approach becomes the main reference in research on firm value (Sabrin, Sarita andSujono, 2016, Sudiyatno andKartika, 2012;Efni, et.al., 2012;Myers, 1984;and Fama, 1980). While research that explains investment decision through asset structure shows the influence of asset structure variable to value (Harc, 2015;Loncan, 2014;Olakunle and Oni, 2014;Harrison and Wicks, 2013;Baert, 2009;Myers, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Montenegro, unlike the case of the Czech Republic or Poland in particular, financial institutions were not actively involved in the process of privatisation. Their primary interest was to take the role of debt holder rather than equity holder in Montenegrin corporations; even though the latter may give banks additional power in the disciplining of firms (Baert and Vennet, 2009). Similarly, although both insignificant, the positive signs on the coefficients on Other_company and Privatization_fund are consistent with this reasoning.…”
Section: Discussion Of the Main Empirical Findingsmentioning
confidence: 53%
“…Namely, although the Montenegrin Law on Accounting and Auditing 7 requires accounting practice in Montenegro to be in line with the International Account-ing and Auditing Standards, there is an evident implementation gap with respect to following IAS in domestic practice. 8 For example, the World Bank's Report on the observance of standard and codes (ROSC, 2007) for Montenegro provides an assessment of accounting, financial reporting, and auditing requirements. The general view on the accounting practice from this report is clear from the following excerpts (ROSC 2007, p. 3): 9 "The review of financial statements identified some systematic accounting issues that need to be properly addressed in practice.…”
Section: Model Specification and Description Of Variablesmentioning
confidence: 99%